Formulation Development and Evaluation of Chronomodulated Drug Delivery Systems for treatment of Diabetes - Arora, Shilpi; Singh, Thakur Gurjeet; Awasthi, Ankit; Dhiman, Sonia (Journal of Neonatal Surgery, 2025)
The research focuses on the formulation development and evaluation of chronomodulated drug delivery systems for anti diabetic drugs, leveraging insights from past studies to optimize the delivery of Vildagliptin microspheres. Chronomodulated drug delivery systems are designed to synchronize the release of medication with the body's natural biological rhythms, enhancing therapeutic efficacy and patient compliance. Vildagliptin microspheres were meticulously prepared using an emulsion solvent evaporation method, guided by previous findings on drug-polymer ratios, surfactant concentrations, and stirring speeds to achieve optimal particle size and drug entrapment efficiency. The microspheres exhibited controlled release properties, essential for maintaining consistent drug levels in alignment with circadian rhythms. Characterization through techniques such as scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and Fourier-transform infrared spectroscopy (FTIR) confirmed the structural integrity and compatibility of the formulated microspheres. The in vitro release studies demonstrated a non-Fickian, zero-order drug release pattern, highlighting the system's potential to deliver Vildagliptin effectively over a prolonged period. The results suggest that the developed Vildagliptin loaded microspheres pulsincap system hold promise for improving the management of diabetes through a chronomodulated approach, warranting further investigation through in vivo studies to establish clinical efficacy and safety.